Formação inicial de professores de Língua Portuguesa: retratos e reflexos do PIBID - Gehring, Fernanda Maria Müller (2016)
The present research has sought to reflect on the possible impacts of the Institutional Program of Scholarship for Teaching Initiation (Programa Institucional de Bolsas de Iniciação à Docência PIBID) on the initial formation of eleven egress students from the subproject Letras/Língua Portuguesa (Languages/Portuguese) 2011-2014, from the State University of the West of Paraná Unioeste campus of Marechal Cândido Rondon Pr. Considering the positive aspects about the Program, we have sought to answer the following question: How did the participation on the subproject impact the initial formation of eleven egress students? To answer this question, we have traced the following specific goals: to verify which the curricular configuration of the Languages Course at Unioeste, campus of Marechal Cândido Rondon is; to identify the role of PIBID as a Public Policy for the teacher s initial formation and also for the student s permanence at the university; to describe the developed activities in the subproject and to verify the effects for the graduating s formation; to verify in which extent the participation in PIBID complemented or not the graduation and the building of being a teacher conception. The research is based on the following theoretical approach: assumptions that rule the teachers formation in Brazil chiefly the Lei de Diretrizes e Bases (LDB 9394/96) and the Diretrizes Curriculares Nacionais para Formação de Professores (CNE/CP 01/2002); teachers initial formation Severino (2012), Gatti (2014), Nóvoa (2012), among others; competences to teach Perrenoud (2000; 2001); teacher-researcher Bortoni-Ricardo (2008), Lüdke (2012a; 2012b), Zeichner (1998), Engel (2000); and the constitution of being a teacher Pimenta (1997), Libâneo and Pimenta (1999), Tardif (2012).The data were generated from the reading of the Pedagogical and Political Project of the Languages course, from the final subproject s report which was sent to CAPES Superior Education Personnel Coordination and from semi-structured interviews with the ex-students. It is, therefore, a research based on the Applied Linguistics, with a qualitative and interpretativist nature. The research reveals interesting data from the egress students point of view about the impacts of PIBID on their teaching formation, specially about the interaction between the teacher in formation and the student from basic education, the approximation of university and school and, consequently, the link between theory and practice.